Effect of the Innominate Bone Horizontal Rotation on Acetabular Version: A Retrospective Radiological Study on a Middle Eastern Population - Ayoubi, Rami; Aouad, Dany; Darwish, Mohammad; Maalouly, Joseph; Hajj, Gerard; Daher, Mohammad; Nehme, Alexandre (International Journal of Clinical Research, 2023)
Background: The impact of acetabular horizontal rotation on the development of femoroacetabular impingement and subsequently osteoarthritis is well-studied in the literature. However, there is not a clear relationship between the rotation of the hemipelvis and the version of the acetabulum. Purpose: The purpose of this study was to evaluate the influence of the rotation of the hemipelvis on the version of the acetabulum. Methods: Through a retrospective study, three-dimensional reconstructions of high-resolution CT (computed tomography) scans of 154 patients receiving pelvic scans for non-orthopedic causes were selected from our institution’s database. The horizontal rotation of the different parts of the hemipelvis was evaluated using the following parameters: superior iliac spine angle (SIS), inferior iliac spine angle (IIS), roof edge angle (REA), equatorial edge angle (EEA) and ischiopubic angle (IPA). Results: The results showed a significant positive correlation between the different angles of the innominate bone and the version of the acetabulum such as when the proximal innominate bone rotates, the cranial part of the acetabulum rotates in the opposite direction. Increased anteversion angles in females compared to males were also observed. Conclusion: The observations suggest that, in an asymptomatic population, the acetabulum should not be considered a separate entity independent from the rest of the innominate bone and that the version of the acetabulum correlates with the rotation of the hemipelvis.